Do Temporomandibular Disorder Patients with Joint Pain Exhibit Forward Head Posture? A Cephalometric Study - Chu-Qiao Xiao; Yi-Dan Wan; Ya-Qi Li; Zhe-Bin Yan; Qiao-Yu Cheng; Pei-Di Fan; Yi Huang; Xiao-Yi Wang; Xin Xiong (Pain Research and Management)
Purpose. To evaluate head and cervical posture in individuals with or without temporomandibular disorders (TMDs) and to assess the correlations between pain, severity of symptoms, and posture. Methods. A total of 384 patients (129 males and 255 females) was included. The Fonseca Anamnestic Index (FAI) was used to assess the severity and prevalence of TMD and the presence of temporomandibular joint (TMJ) pain. Patients were divided into three groups: the TMD-free group, TMD without TMJ pain group, and TMD with TMJ pain group. Subsequently, the patients with TMJ pain were further divided into mild TMD and moderate/severe TMD groups. Nine parameters were traced on cephalograms to characterize the head and cervical posture. Results. TMD patients with TMJ pain showed increased forward head posture (FHP) than patients without TMJ pain and TMD-free subjects. No significant difference was observed between the TMD patients without TMJ pain and TMD-free subjects. In the TMD patients with the TMJ pain group, the moderate/severe TMD patients demonstrated increased FHP compared to mild TMD patients. TMD patients with joint pain had greater CVT/RL (B = 3.099), OPT/RL (B = 2.117), and NSL/C2’ (B = 4.646) than the patients without joint pain after adjusting for confounding variables (P<0.05). Conclusion. TMD patients with TMJ pain showed increased FHP compared to other groups, and FHP became more significant as TMD severity increased in male patients, indicating the FHP might play an important role in the development of TMJ pain. In the clinical assessment of TMD, the patients’ abnormal head and cervical posture might be considered.